The role of the chemical structure of an anionic polyelectrolyte on the formation of a structure of polyelectrolyte complexes based on poly-(4-vinylpyridine) hydrochloride - Shtompel, V. I.; Riabov, S.V.; Polischuk, T.A.; Kercha, Yu.Yu. (Reports of the National Academy of Sciences of Ukraine, 2014)
By using the methods of wide- and small-angle x-ray scattering, the structures of two types of polyelectrolyte complexes based on Na-salt carboxymethylcellulose or Na-salt of polymethacrylic acid and hydrochloride are investigated. It is shown that, in a volume of polyelectrolyte complexes based on Na-salt carboxymethylcellulose, a layered quasicrystalline structure is formed, whereas the polymer systems based on Na-salt of polymethacrylic acid have predominantly an amorphous structure similar to that of the initial anionic polyelectrolyte.